Building Human Capital : Lessons from Country Experiences - Ireland - World Bank (World Bank, Washington, DC, 2021)
Over the last sixty years, Ireland has experienced profound economic, social, technological, occupational, cultural, and demographic changes. It has emerged from the most recent economic crisis stronger than ever and remains committed to its vision of a nation of people armed with the relevant knowledge, entrepreneurial agility, and analytical skills to support economic and social prosperity and to enhance the well-being of the country. Education has been at the heart of this transformation and has been a central component of Ireland’s human capital development. Ireland’s journey towards prosperity has not been without challenges, and some of these are acknowledged in this case study. The first part of the case study looks at the story of Ireland’s remarkable economic and social transformations since the 1960s, with a focus on the contribution made by education. The opening section sets the context and notes a number of macroeconomic features that have contributed to the creation, maintenance, and development of a business environment that establishes Ireland as a cost-effective and attractive place to live and work The second section charts the story of education success in Ireland.